Performance Evaluation of Bagging Meta-Estimator in Lung Disease Detection: A Case Study on Imbalanced Dataset - Azdy, Rezania Agramanisti; Syam, Rahmat Fuadi; Faizal, Edi; Sumiyatun, Sumiyatun (Yocto Brain, 2023)
In this study, titled